Project-based learning through STEM approach: Is it effective to improve students' creative problem-solving ability and metacognitive skills in physics learning?. Issue 1 (February 2021) - Fiteriani, Ida; Diani, Rahma; Hamidah, Athi'; Anwar, Chairul
Abstract: This study was aimed to determine the effect size of the PjBL learning model with the STEM approach in improving students' creative problem-solving ability and metacognitive skills in physics learning. The results of the data analysis showed that there was an influence of the application of the PjBL learning model with the STEM approach toward students' creative problem-solving ability and metacognitive skills. The creative problem-solving ability score obtained by the experimental class was 0.39 while the control class obtained a score of 0.30. in terms of metacognitive skills, the experimental class obtained a value of 0.30 while the control class obtained a value of 0.20. The PjBL learning model with the STEM approach was more effective in increasing the students' creative problem-solving ability and metacognitive skills indicated by obtained effect size value of 0.72 and the effect size of the metacognitive skill of 0.64 in the medium category. Based on the results of the MANOVA test, the creative problem-solving ability and metacognitive skills were less than 0.05 (sig <0.05). It can be concluded that there was an effect of the application of the PjBL learning model with the STEM approach toward students' creative problem-solving ability and metacognitive skills in physics learning.